Comparison Between Aristotle and Ibn Sina Regarding the Theory of the Active Intellect - Khamoush, Ahmad Naweed Rahimi; Masruri, Hadi; Yousuf, Salih Abdulrahman Alsounusi (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
This study examines the concept of the “Active Intellect” (al-‘aql al-fa‘āl) in the philosophies of Aristotle and Avicenna through a comparative analytical approach based on their primary works, De Anima and The Book of Healing. The research is motivated by the importance of understanding the development of the concept of intellect in the history of philosophy and its role in linking knowledge, the soul, and reality. In addition, the study highlights the relevance of philosophical texts in Arabic language education, particularly in fostering critical thinking and conceptual understanding. The objective is to identify similarities and differences between the two philosophers and to trace the transformation of the concept from the Greek to the Islamic context. The method employed is a descriptive-analytical comparative approach based on close textual reading. The findings show that both philosophers agree on the cognitive function of the Active Intellect as the actualizer of intellectual potential, yet differ in its ontological and metaphysical foundations. Aristotle’s account remains ambiguous, whereas Avicenna provides a more systematic cosmological framework. This study concludes that the concept of the Active Intellect is not only philosophically significant but also pedagogically relevant for Arabic language teaching through philosophical texts.